Deep knowledge of B2B relationships within and across borders - Woodside, Arch; Baxter, Roger, 1944- (Advances in business marketing & purchasing, 2013)
The common thread of the five papers in this volume is that making sense and achieving deep knowledge of three-plus B2B relationships are necessary antecedents for achieving high operating effectiveness, high (on-time) efficiency, and sustaining profits for each firm in these relationships.